Alteraciones tempranas del sistema nervioso central en un modelo experimental de encefalopatía hepática mínima - Tallis, Silvina (2014)
Liver failure, regardless of its etiology, is defined as a claudication in liver function\nresulting in a broad range of clinical, biochemical and neurophysiological changes.\nHepatic disease may have an acute or chronic presentation. The most important\ncomplications of the chronic stage, and less frequently acute, are Portal Hypertension\nSyndrome and Hepatic Encephalopathy.\nHepatic Encephalopathy is a clinical situation in which medical science has had less\ncontrol over the other issues and that arise as complications of liver cirrhosis. Hepatic\nEncephalopathy is defined as a potentially reversible syndrome that refers a wide\nspectrum of neurological and psychiatric alterations, which can range from subtle\nchanges in behavior to deep coma and death. This neuropsychiatric syndrome is\nsecondary to hepatic dysfunction, the development of porto-systemic circuits or a\ncombination of both. The clinical picture is complex and can affect any brain area. The\nalteration is an organic mental reaction with a neurological and pshychiatric disorder.\nAn important feature is the variability, especially in the chronic forms. The findings\ndepend on the nature and intensity of the etiology and predisposing factors. At\npresent, Hepatic Encephalopathy is considered a great intellectual challenge in various\nmedical fields because of its varied clinical picture, its complex pathophysiology, the\nmultiplicity of precipitating factors, lack of a single causal phenomenon, as well as due\nto the lack of additional confirmatory studies and diagnostics.\nMinimal Hepatic Encephalopathy is a subclinical stage having a chronic\npathophysiological development associated with a cerebral adaptive process. The\nexhaustive study of Minimal Hepatic Encephalopathy is a useful tool to identify the\npathways that initiate or trigger the pathophysiological mechanisms that subsequently\ninteract in advanced stages. Once triggered, the condition becomes complex that it is\ndifficult to ascertain what has been the pathway or starter mechanism.\nThe main objective of the present Doctoral Thesis was to study the early alterations of\nthe Central Nervous System in an experimental model of Prehepatic Portal\nHypertension and to characterize Minimal Hepatic Encephalopathy induced by the\nPartial Portal Vein Ligation, in a morphological and functional study of neurons,\nastrocytes and capillary vessels. For the first time, in an experimental model of\nMinimal Hepatic Encephalopathy, structural and functional changes in the\nhippocampus and in the cortex of Minimal Hepatic Encephalopathy animals are\ndescribed. At 10 days after surgery, the Minimal Hepatic Encephalopathy group\nfulfilled with the essential features of the Hepatic Encephalopathy type B associated\nwith portosystemic shunts without intrinsic hepatocellular disease. The findings\ndescribed in this Doctoral Thesis suggest that Minimal Hepatic Encephalopathy has\nCentral Nervous System alterations that are focal and differential according to the\naffected area and that the described alterations were associated with moderate\nhyperammonemia, main feature of Hepatic Encephalopathy.\nThe understanding of the pathogenesis of Minimal Hepatic Encephalopathy would\nprovide a theoretical framework that could contribute to the understanding of the\npathophysiology of Hepatic Encephalopathy in order to find an early biochemical\nmarker of Hepatic Encephalopathy. Also contribute greatly to the development of\nappropriate diagnostic and therapeutic treatment.